2014
DOI: 10.2478/acve-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

First Report on Centrorhynchus Aluconis in Common Buzzard (Buteo Buteo) in Northwest Iran

Abstract: In July 2012 a male Common Buzzard (Bute obuteo) from the Department of Environment of East Azerbaijan was sent to the Parasitology Laboratory at the School of Specialized Sciences of Veterinary Medicine, Science and Research Unit, Tehran Islamic Azad University. Gastrointestinal parasites were isolated and sent to the Iranian National Parasitology Museum in order to specify the diagnosis. It was determined that the bird was infected with the acanthocephalan Centrorhynchu saluconis. This is the fi rst report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For instance, C. aluconis is considered as an owl parasite in Europe (Kutzer et al, 1982;Kritscher 1985;Ewald & Crompton, 1993;McInnes et al, 1994;Sitko 1994;Dimitrova et al, 1995;Ferrer et al 2004;Dimitrova & Dimitrova 2012;Santoro et al, 2012b;Lisitsyna & Greben, 2015), but it has sometimes been observed also in diurnal raptors (Yamaguti 1963, Illescas Gomez et al 1993Borgsteede et al 2003, Sitko 2011. On the other hand, C. buteonis has been documented not only in Falconiformes and Accipitriformes, but also in owls, especially in the Strix genus (Furmaga, 1957;Yamaguti, 1963;Michálek, 1984;Kritscher, 1985;Sitko 2011;Dimitrova & Dimitrova, 2012;Shirazi et al, 2014). The widest host range, as confi rmed by the above mentioned authors, was observed in C. globocaudatus, primarily infecting diurnal raptors (Sanmartín et al, 2004;Lisitsyna & Greben, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…For instance, C. aluconis is considered as an owl parasite in Europe (Kutzer et al, 1982;Kritscher 1985;Ewald & Crompton, 1993;McInnes et al, 1994;Sitko 1994;Dimitrova et al, 1995;Ferrer et al 2004;Dimitrova & Dimitrova 2012;Santoro et al, 2012b;Lisitsyna & Greben, 2015), but it has sometimes been observed also in diurnal raptors (Yamaguti 1963, Illescas Gomez et al 1993Borgsteede et al 2003, Sitko 2011. On the other hand, C. buteonis has been documented not only in Falconiformes and Accipitriformes, but also in owls, especially in the Strix genus (Furmaga, 1957;Yamaguti, 1963;Michálek, 1984;Kritscher, 1985;Sitko 2011;Dimitrova & Dimitrova, 2012;Shirazi et al, 2014). The widest host range, as confi rmed by the above mentioned authors, was observed in C. globocaudatus, primarily infecting diurnal raptors (Sanmartín et al, 2004;Lisitsyna & Greben, 2015).…”
Section: Discussionmentioning
confidence: 77%